O halucinogenním oříšku v naší kuchyni - Jurášek, Michal; Drašar, Pavel (Chemické listy, 2023)
The article describes the nutmeg of a nutmeg tree (Myristica), which is used as a spice and traditional medicine but is also abused as an illicit drug. The main chemical components, namely myristicin, are described.
Keywords: léčivé rostliny; Narcotics; halucinogeny; Plant Poisoning; otrava rostlinami; Plants, Medicinal; Myristica; Plant Oils; oleje rostlin; Hallucinogens; Spices; koření; narkotika